Psalms and hymns in the language of the Cree Indians of the Diocese of Saskatchewan, North-West America [electronic resource] - Mackay, J. A. (John Alexander), 1838-1923 (London : Printed for the Society for Promoting Christian Knowledge, 1891)
Text in syllabic and roman characters. In double columns. Electronic reproduction. Mode of access: Internet. 44